2014
DOI: 10.1089/bfm.2014.0077
|View full text |Cite
|
Sign up to set email alerts
|

Centralized Breastmilk Handling and Bar Code Scanning Improve Safety and Reduce Breastmilk Administration Errors

Abstract: Safe handling and preparation of breastmilk within the hospital setting are often taken for granted, and the process may not be scrutinized until problems arise. Areas of concern focus on both risk of contamination of breastmilk feedings due to handling and fortification and risk of a breastmilk misadministration. In two phases, Children's Hospital of Orange County (Orange, CA) implemented centralized breastmilk handling and breastmilk bar code scanning. As a result of these process changes, reports of breastm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 1 publication
0
46
0
Order By: Relevance
“…The limited oral feeding skills of many preterm infants often results in human milk being administered via an enteral feeding tube ( 4 ). In addition, fortification is commonly required to promote optimal growth and development—particularly in the smallest of preterm infants ( 2 , 4 , 5 ). Consequently, a mother's own milk must be pumped, labeled, transported to the hospital, stored, tracked for appropriate expiration dates and times, thawed (if previously frozen), fortified, and administered to the infant with care taken at each step of the process to avoid microbial contamination, misadministration (the wrong milk for the wrong patient), fortification errors, and waste ( 1 – 5 ).…”
mentioning
confidence: 99%
“…The limited oral feeding skills of many preterm infants often results in human milk being administered via an enteral feeding tube ( 4 ). In addition, fortification is commonly required to promote optimal growth and development—particularly in the smallest of preterm infants ( 2 , 4 , 5 ). Consequently, a mother's own milk must be pumped, labeled, transported to the hospital, stored, tracked for appropriate expiration dates and times, thawed (if previously frozen), fortified, and administered to the infant with care taken at each step of the process to avoid microbial contamination, misadministration (the wrong milk for the wrong patient), fortification errors, and waste ( 1 – 5 ).…”
mentioning
confidence: 99%
“…14 Others have shown that BCMA systems for human milk reduce wrong milk errors. 17,24,27 As our study and other studies have demonstrated, 24 BCMA has highlighted new, previously unmonitored scanned errors, such as the potential for feeding expired milk 24 or incorrectly prepared milk.…”
Section: Figurementioning
confidence: 63%
“…The effort to reduce scanned and actual errors was based on previously defined best practices for breast milk administration. 23,24 W&I was implemented for use by nurses to check in, prepare, and administer EBM feedings via centralized scanners. At this time, bedside medication barcoding was unavailable in the NICU; therefore, to use W&I optimally, scanners had to be purchased.…”
Section: Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…An EN order set that includes these details for the diet order and orders for laboratory monitoring, assessment of tolerance, and consults could be developed by organizations . Implementation of scanning software with the EHR would increase the accuracy of delivering the right product to the right patient at the right time, as has been demonstrated in the neonatal intensive care unit and children's hospitals …”
Section: Nutrition Care Plan and Interventionmentioning
confidence: 99%